Pemberdayaan KWT Dewi Sintha II dalam Program Pekarangan Pangan Bergizi di Desa Ngropoh - Putri, Noviana; Septiana, Ananda Devika Nur; Salmi, Annisa Fitri Nur; Aulia, Annisa Syifa; Ananda, Desinta Fitri; Utami, Nisabela Dian; Verdasa, Chairudin Iska; Arbi, Fathoni Mufied; Padmaningrum, Dwiningtyas (Nur Science Institute, 2025)
Food security is a critical issue of global and national concern. The Nutritious Food Yard Program (P2B) was introduced as a solution to enhance food security at the household level through community empowerment. According to the Food Insecurity Experience Scale (FIES), Temanggung Regency is categorised as an area with a relatively high level of food insecurity. This community service program aims to analyse and describe the implementation process and the impact of empowerment initiatives for the Dewi Sintha II Women Farmers Group (KWT) in Ngropoh Village by applying the Participatory Rural Appraisal (PRA) approach. Over three months, various yard-based training activities were conducted, including the production of husk charcoal, liquid organic fertiliser (POC), KOHE fertiliser, seed germination, polybag cultivation, aquaponics (BUDIKDAMBER), food processing, and product marketing. The results of pre-test and post-test assessments showed a significant improvement in members’ knowledge and skills. High levels of enthusiasm and active participation reflected the effectiveness of the PRA approach in fostering awareness and household food independence.